De morbis acutis et chroniis - Anonymus Parisinus. (Studies in Ancient Medicine, 1997)
This volume is the first complete critical edition of the Greek medical work of the 1st century A.D. on acute and chronic diseases, by an anonymous writer commonly known as Anonymus Parisinus Darembergii sive Fuchsii. The work includes an introduction, a critical text with apparatus and an English translation accompanied by a commentary on textual, linguistic and factual problems. There is an index of Greek words and an index of drugs and foods. This edition is important both because it is the first complete edition (the former, by Fuchs, being confined to the first half of the work), and because it is based on all four manuscripts that preserve the work (Fuchs employed two of them).